Estudo de caso: percepção sobre a necessidade de mudanças no setor de fisioterapia do CMS - Barnetche, Carmen Beatriz Pozo (Universidade do Vale do Rio dos Sinos, 2013)
Nowadays the Enterprises considered well succeeded have a conviction in common, in speech as well as in practice: success is on the hands of the people who operate them, in higher or lower degree all the Organization depends the human performance. In line with this conviction, this study has the objective of finding and revealing the perceptions of the people of the physiotherapy sector of CMS in relation to the need of changing. People were brought think and reflect about what to change and why to change. The theoretical framework guiding the practices data and possibilities arising therefrom. Respondents perceive the need for change in relation to attitudes and behavior as well as the ability to offer new products in the treatment of patients.
Keywords: Gestão de pessoas; Mudança organizacional e desenvolvimento profissional; Personal management; Organizational change and development professional